Identification and characterization of CmPP2C31 playing a positive role in the abiotic stress resistance of Chinese chestnut via an integrated strategy - Wang, Xuan; Shang, Wenli; Li, Mingyuan; Cao, Fei; Wang, Dongsheng; Wang, Meng; Lu, Yi; Zhang, Haie; Shen, Fei; Liu, Jing (Frontiers in Plant Science, 2024)
Chinese chestnut (Castanea mollissima Blume) is an important economic forest tree species and mainly cultivated in mountainous areas and wastelands, subjecting it to various abiotic stresses. The protein phosphatase 2C (PP2C) genes contributes largely to stress responses in plants. However, the characteristics and functions of PP2C genes in C. mollissima remain unknown. This study provides comprehensive analyses (including phylogenetic, synteny, RNA-seq, transgenic and yeast one-hybrid methods) revealing the characteristics of CmPP2C gene, which plays an important role in response to abiotic stress. Here, we identified 68 CmPP2Cs in the Chinese chestnut genome, and analyzed their characteristics and phylogenetic relationships. Furthermore, synteny analysis revealed that segmental and tandem duplication drove the expansion of the CmPP2C family to adapt to natural environmental pressures. RNA sequencing and co-expression analyses indicated that four hub CmPP2Cs in two key modules probably play important roles in the resistance to abiotic stress in chestnut. Among them, CmPP2C31 was significantly down-regulated under drought stress. Transgenic experiments via pollen magnetofection revealed that CmPP2C31 could positively and significantly regulate the drought resistance of Chinese chestnut seedlings. Subcellular localization showed that CmPP2C31 was a nuclear protein. Yeast one-hybrid assays suggested that EVM0007407 could regulate CmPP2C31 expression by binding to its promoter, thereby participating in abiotic stress resistance. These findings in our study provided detailed information on the CmPP2C family genes and laid a foundation for further elucidating the molecular mechanism of resistance to abiotic stress chestnut.